(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Shared care planning is a tool with great potential, but its effective application depends on understanding and applying key philosophical premises. This essay explores four critical premises: implicit anthropology, the conception of autonomy, the notion of medicine, and the model of the doctor-patient relationship. We aim to demonstrate that successful shared care planning requires adopting a more phenomenologically accurate perspective on illness, medicine, and the patient-caregiver relationship. Furthermore, we advocate for educational programs that cultivate a deeper appreciation of what it means to respect and support autonomous yet inherently vulnerable individuals.